Mineral Composition of Traditional Non-GMO Soybean Cultivars in relation to Nitrogen Fertilization - Bogdan Szostak; Aleksandra Głowacka; Renata Klebaniuk; Anna Kiełtyka-Dadasiewicz (The Scientific World Journal)
Soybean is widely used as food. Genetic factors, as well as agrotechnical procedures, affect the yield and quality of soybeans. The subject of our research was the synchronization between soil N supply (from both mineralization and fertilization) and crop N demand. The aim of the research was to determine the effect of the cultivar and nitrogen application on the seed yield and mineral content in soybeans. Two non-GMO soybean cultivars (Amandine and Merlin) and four mineral nitrogen fertilizers ((A) N 0, control; (B) N 30:0, 30 kg N ha−1 before sowing; (C) N 0:30, 30 kg N ha−1 at BBCH 73–75; (D) N 30:30, 30 kg N ha−1 before sowing and 30 kg N ha−1 at BBCH 73–75) were tested. The highest soybean yield was obtained following nitrogen application at a rate of 60 kg ha−1. The genetic factor was found to significantly influence the content of some macronutrients (P, K, and Mg) and micronutrients (Cu, Mn, and Fe). In general, the Merlin cultivar had better macronutrient parameters except nitrogen, while Amandine had a higher content of Cu and Fe. Nitrogen fertilization decreased the content of P, K, and Zn in the soybeans but significantly increased the content of Ca, Mg, Cu, and Mn.